2006
DOI: 10.1097/01.mlg.0000243043.65560.3f
|View full text |Cite
|
Sign up to set email alerts
|

Can [18F]-Fluorodeoxyglucose Standardized Uptake Values of PET Imaging Predict Pathologic Extrathyroid Invasion of Thyroid Papillary Microcarcinomas?

Abstract: The SUVs from FDG PET imaging alone cannot predict the pathologic extrathyroid invasion in patients with TPMC. However, the ultrasonographic findings, such as tumor site, provide better information about the extrathyroid invasion of TPMC tumor foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 15 publications
2
69
4
Order By: Relevance
“…However, there were also conflicting reports [1][2][3]6] that those parameters are not an independent predictor of 18 F-FDG uptake in PTC, as shown in our study. These results might reflect that the high 18 F-FDG uptake in cancer cells is not necessarily the consequence of rapid proliferation, but is caused by the activation of oncogenic pathways that regulate transporters and enzymes involved in the metabolism of glucose [18].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, there were also conflicting reports [1][2][3]6] that those parameters are not an independent predictor of 18 F-FDG uptake in PTC, as shown in our study. These results might reflect that the high 18 F-FDG uptake in cancer cells is not necessarily the consequence of rapid proliferation, but is caused by the activation of oncogenic pathways that regulate transporters and enzymes involved in the metabolism of glucose [18].…”
Section: Discussioncontrasting
confidence: 69%
“…However, reports regarding the associations of other factors and the 18 F-FDG uptake are inconsistent. Several studies have shown that the 18 F-FDG avidity of PTC is related to known poor prognosis factors [4], such as lymph node metastasis [2,5] and perithyroidal extension [5], although there are conflicting results [1][2][3]6].…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al (2006b) reported a strong correlation between SUV and EE of papillary microcarcinoma in a univariate analysis; however, associations between SUV and EE or other aggressive tumor features were not significant in a multivariate analysis. Also, there was no significant difference in the SUV of papillary macrocarcinoma according to the presence or absence of EE (Choi et al 2011b).…”
Section: Preoperative Assessment Of Thyroid Cancer With Fdg Petmentioning
confidence: 99%
“…Jeong et al (2006b) reported that the SUV of thyroid cancer alone is not predictive of the presence of EE, lymphatic metastasis, or the multiplicity of thyroid cancer. Although no studies have evaluated the association between prognosis and FDG uptake, several support the hypothesis that FDG PET before surgery has prognostic value in DTCs.…”
Section: Prediction Of Prognosis By Fdg Pet In Patients With Dtcsmentioning
confidence: 99%
See 1 more Smart Citation